PENGARUH KECERDASAN EMOSIONAL, PELATIHAN DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU DI SMPN 1 KECAMATAN LUAK KABUPATEN LIMA PULUH KOTA - Adrizal, Adrizal; Putri, Anne (Jurnal Ekonomi, 2020)
This study aims to look at the influence of emotional intelligence, training and work environment on teacher performance in SMPN 1 Luak District, Lima Puluh Kota. This type of research is quantitative research using survey methods. The sample in this study were 35 teachers with PNS and Non PNS status. The data analysis method used is SEM (Structural Equation Modelin ) analysis technique based on PLS ( Partial Lea st Square) variance .Data collected through questionnaires, interviews and documentation studies. The results of this study indicate that emotional intelligence has a significant positive effect on teacher performance. The higher the emotional intelligence, the higher the teacher's performance. This is indicated by the value of the original sample (coefficient) of emotional intelligence variables of 0.524, and p-value of 0.000. Training has a significant positive effect on teacher performance. The better the training, the better the teacher's performance, this is indicated by the value of the original sample of training variables of 0.296 and p-value of 0.034. The work environment has no effect on teacher performance. This is indicated by the original sample value of the work environment variable of 0.180 and the p-value of 0.165 which is greater than the alpha of 0.05.Keywords : Emotional Intelligence, Training, Work Environment, Teacher PerformanceThis study aims to look at the influence of emotional intelligence, training and work environment on teacher performance in SMPN 1 Luak District, Lima Puluh Kota. This type of research is quantitative research using survey methods. The sample in this study were 35 teachers with PNS and Non PNS status. The data analysis method used is SEM (Structural Equation Modelin ) analysis technique based on PLS ( Partial Lea st Square) variance .Data collected through questionnaires, interviews and documentation studies. The results of this study indicate that emotional intelligence has a significant positive effect on teacher performance. The higher the emotional intelligence, the higher the teacher's performance. This is indicated by the value of the original sample (coefficient) of emotional intelligence variables of 0.524, and p-value of 0.000. Training has a significant positive effect on teacher performance. The better the training, the better the teacher's performance, this is indicated by the value of the original sample of training variables of 0.296 and p-value of 0.034. The work environment has no effect on teacher performance. This is indicated by the original sample value of the work environment variable of 0.180 and the p-value of 0.165 which is greater than the alpha of 0.05.